Advancing Human Rights in the International Investment Law Regime Through Effective Public Participation : A Kenyan Perspective - Kabre, Rimdolmsom Jonathan (University of Pretoria, 2021)
Mini Dissertation (LLM)--University of Pretorai, 2021.